Ultrasonographic measurements of localized fat accumulation in Shetland pony mares fed a normal v. a high energy diet for 2 years. (4th December 2017) - Siegers, E. W.; de Ruijter-Villani, M.; van Doorn, D. A.; Stout, T. A. E.; Roelfsema, E.
Abstract : Health risks associated with obesity are more likely a factor of the localization of fat excess, rather than of elevated BW per se . The aim of this randomized controlled clinical trial was to determine the effect of a long-term high energy diet on BW, fat accumulation and localization. Eight Shetland pony mares, 3 to 7 years old, were randomly divided into a control and a high energy (HE) diet group fed either maintenance or double maintenance energy requirements (200% net energy (NE)) for two consecutive summers, with a low energy diet in the winter in between. Body condition score (BCS) did not differ between the groups at the onset of the study (control 5.6±0.75 v . HE 6.3±0.5). From 12 weeks after starting the diet, ultrasonography of five different locations (retroperitoneal, axillary, withers, intercostal and rump) for adipose deposition, BCS and BW were measured monthly during the period that ponies received different diets. Statistical analysis was performed using a linear mixed-effects model with post hoc Bonferroni testing. P values <0.05 were considered significant. At week 12 after the onset of the diet, fat thickness in the HE group was significantly greater than in the control group. During the monitoring period, the HE group showed a significant increase in mean (±SE) BW (+52%, 265±13.94kg) and BCS (+70%; to 9.0±0.4), while the control group was unchanged (BW 160±13.98 kg; BCS 3.8±0.4). At all locations, the fat depth in the HE group increased significantly, with the highest increase noted for retroperitoneal deposits. The conclusions were that a 200% NE diet induced subcutaneous and retroperitoneal fat accumulation, with the greatest increase in intra-abdominal deposits. The moderate increase of the subcutaneous fat depth followed by a plateau phase suggests the existence of a limit of adipose tissue expandability, as in man.